Business Strategy and Hybrid Models in Indonesia's Mice Industry Post Covid-19: Impacts, Policies, and Development Potential - M. Amboro Alfianto; Awkila Nathanael Odoh; Muhammad Alandra Bestama; Lazia Putri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This quantitative study uses SmartPLS3 to analyze the main issues related to the impact of the COVID-19 pandemic on MICE (Meeting, Incentive, Convention, and Exhibition) business actors, as well as the role of the hybrid model in maintaining the sustainability of MICE activities in Indonesia. This study focuses on five representative cities that are the main targets of MICE activities according to the government's strategic plan, namely Jakarta, Bogor, Bali, Yogyakarta, and Malang. The COVID-19 pandemic that has hit various countries, including Indonesia, for more than a year, has brought major challenges. The tourism and MICE sectors are among the most affected, with many business actors forced to stop their operations and switch to alternative sectors such as culinary, agriculture, and plantations as a means of survival. However, the emergence of the hybrid model has become an important solution for the MICE sector. Some alternative solutions adopted during the pandemic include organizing virtual MICE events, virtual tourism, webinars, and meetings through platforms such as Google Meet and Zoom. Teleconferencing has also become an important tool to maintain engagement. These adaptations highlight the increasing reliance on advanced technology to ensure the sustainability of the MICE industry. The implementation of these activities requires high creativity and quality in order to run well. This change emphasizes the importance of continuous innovation and utilization of technology by MICE industry players to navigate the ever-evolving landscape.